Investigation of mutations in exon 14 of SH3TC2 gene and exon 7 of NDRG1 gene in Iranian Charcot Marie Tooth type 4 patient - Moosavi, Rahmaneh; Jahangir Soltani, Niloofar; Houshmand, Massoud (Iranian Journal of Child Neurology, 2020)
CMT4 is an autosomal recessive form of Charcot-Marie-tooth disease which has shown more severity and earlier age of onset compared to other types of it, furthermore; CMT4C andCMT4D are the more prevalent types in Mediterranean countries due to higher incidence of consanguineous marriages. The most important aim of this study is to illuminate the rate of p.R148X mutation in NDRG1 gene and p.R1109X in SH3TC2 gene which are responsible genes for CMT4D and CMT4C respectively in Iranian population, Furthermore; this study investigated the probable other nucleotide changes in exon 14 of SH3TC2 gene and exon 7 of NDRG1 gene. In order to study this disease, 24 CMT4 affected individuals that they referred to Iran Special Medical Center, were clinically and electrophysiologically evaluated and selected for this study. The patients’ DNA was extracted from blood samples and after PCR, the products were sequenced and analyzed by Finch TV software. None of the founder mutations we were searching for were seen in this study. Sequencing of SH3TC2 gene showed SNP rs1025476 (g.57975C>T) in 21 patients (87.5%) that 7 individuals were homozygous and 14 individuals were heterozygous for this variant. Despite of high rate of considered mutations in some specific populations it seems that these mutations are very rare in Iranian CMT4 affected individuals. To clarify the association of SNP rs1025476 with CMT4, further assesments are needed and it could be helpful in knowing the Iranian population genetic markers and their genetic features.